Influence atoms of Co, Ni, Cu on the catalytic activity of small Pt clasters: First principles calculations - Chernikova, O. M.; Mateik, H. D.; Ogorodnik, Y. V. (Physics and Chemistry of Solid State, 2020)
Based on the calculations from the first principles, we obtained the distributions of valence electron densities and electronic energy spectra for small Ptn clusters (where n = 1-5 atoms). According to the results of calculations, it is determined that the inclusion of oxygen atoms or atoms of other kinds in small Ptn clusters, as a rule, affect the catalytic activity of research systems. It is established that during doping of small platinum clusters by atoms of 3-d transition metals (Cu, Ni, Co), the electronic structure of the cluster and the band gap change. This in turn helps to increase the catalytic activity of platinum.